EFEKTIVITAS PROGRAM PENDAMPINGAN SERTIFIKASI HALAL SELF DECLARE DI KABUPATEN SUMBAWA - Okta Handayani; Roos Nana Sucihati (Pusat Riset dan Publikasi, 2025)
This study aims to know the effectiveness of halal product certification assistance in the self-declare program in Sumbawa district. The type of this study was descriptive study using quantitative approach. The numbers of respondents in this study were 94. The tool used to collect data were questionnaires. The data analysis tool used was Importance Performance Analysis which consists of 3 indicators, namely program success, target success, and satisfaction with the program. The results of study showed that the assistance had done by mentor of halal product had been effective or in accordance with what was expected by respondents, in this case business actors who had been facilitated to obtain halal product certification through the self-declare program. Furthermore, based on the results of the Importance Performance Analysis, it showed that the effectiveness degree of the assistance had done by Halal product was in accordance with what were expected by respondents or business actors it was based by the results of the average respondent suitability level calculation of 98%, it means that business actors felt satisfied with 15 attributes. which has been tested.